2008
DOI: 10.2174/1874440000802010106
|View full text |Cite
|
Sign up to set email alerts
|

Increased Brain Activation During the Processing of Spatially Invalidly Cued Targets

Abstract: Abstract:In a spatial central cue Posner´s paradigm, positions in the vertical meridian were cued in order to evaluate the neuro-cognitive consequences in the processing of validly cued (VC) and invalidly cued (IC) targets. Sixty-four EEG channels were recorded and analyzed showing that IC targets produced an enhanced P3 component with respect to VC targets. With the purpose of reinforcing the idea of increased activation during IC targets and to define the areas in which the increased activation would occur, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
6
0
1
Order By: Relevance
“…Similar findings have been demonstrated using magneto- and electroencephalographic (M/EEG) methods probing the temporally-sensitive dynamics (e.g., Gómez et al 2008 ). For instance, in healthy adult populations, neural oscillatory activity related to attentional reorienting in the theta (4–8 Hz), alpha (8–14 Hz), and beta (14–24 Hz) bands has been detected in the superior parietal and intraparietal sulcus, along with the FEF, inferior frontal gyrus, and prefrontal cortices ( Arif et al, 2020a ; Proskovec et al, 2018a ).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar findings have been demonstrated using magneto- and electroencephalographic (M/EEG) methods probing the temporally-sensitive dynamics (e.g., Gómez et al 2008 ). For instance, in healthy adult populations, neural oscillatory activity related to attentional reorienting in the theta (4–8 Hz), alpha (8–14 Hz), and beta (14–24 Hz) bands has been detected in the superior parietal and intraparietal sulcus, along with the FEF, inferior frontal gyrus, and prefrontal cortices ( Arif et al, 2020a ; Proskovec et al, 2018a ).…”
Section: Introductionsupporting
confidence: 77%
“…They did not show the same exhaustion of resources as their younger counterparts; rather, older youth showed a pattern of necessary and increasing engagement with more toxic exposure. Several previous studies of attentional reorientation have reported validity effects in the parahippocampal area ( Gómez et al, 2008 ; Vossel et al, 2006 ). Research suggests that parahippocampal activity related to attentional reorientation during invalid trials may be connected to revision of the task model due to the critical role of the hippocampus and parahippocampal area in forming transient memory traces of the characteristics within an environment ( Gómez et al, 2008 ).…”
Section: Discussionmentioning
confidence: 98%
“…A recent MEG study found the late positive potential, which is sensitive to stimulus saliency, and Pe, to share similar STS sources (Helenius et al, 2010 ). The ventral cortical attentional saliency network involving IFG/AI, STG, temporo-parietal junction, and inferior parietal lobe, is sensitive to stimulus novelty and is the neural basis of the P3 potential response to novelty (e.g., Horn et al, 2003 ; Mulert et al, 2004 ; Gómez et al, 2008 ; Li et al, 2009 ), and fMRI regions that correlate with the amplitude of the P3 are insula, thalamus and right medial frontal gyrus (Horovitz et al, 2002 ). The stimulus-preceding anticipatory relatively right-lateralized negative potential that precedes aversive stimuli and feedback and seems to depend on its affective–motivational properties, was localized into the IFG/AI (Böcker et al, 1994 ; Lavric et al, 2008 ; Kotani et al, 2009 ; see also Brunia et al, 2000 ; Stern and Mangels, 2006 ).…”
Section: Orienting and Ifg/ai Top-down Control Reflected In Fmri Eegmentioning
confidence: 99%
“…Thus, independent of emotional presence or absence, spatial validity corresponded inversely to the P3a-activity. With spatial cueing the P3a has been so far mainly investigated with predictive designs (i.e., 75% valid vs. 25% invalid conditions), where the low probability of invalid stimuli increases their novelty character of spatial position [ 16 , 24 , 28 , 29 ]. However, while the P3a validity differential activation might be larger in predictive cueing, it was still present in the current unpredictive cueing design (50% valid/invalid).…”
Section: Discussionmentioning
confidence: 99%